"My kid is going through a growth spurt—What should I do?" Taking an interdisciplinary approach to athletic development during the adolescent growth spurt - Johnson, D.; Eisenmann, J.; Lawson, R.; Stables, R.; Williams, S.; Cumming, S.; Lloyd, R. S. (Strength and Conditioning Journal, 2025)
Puberty is a critical period for young athletes, characterized by significant physical, psychological, and social changes. During puberty, young athletes experience the adolescent growth spurt at the same time as intensified training regimens, which can affect performance, injury risk, and overall health. Systematic training can improve physiological and performance outcomes, but the increased training volume and changes to the body during adolescence can also heighten the risk of injuries. This article discusses the injury risks associated with adolescent growth and provides comprehensive recommendations to mitigate these risks. Key recommendations include limiting training hours to the athlete's age, monitoring growth and maturation to adjust training loads and content, and incorporating and modifying consistent strength and conditioning prescriptions. In addition, optimal nutrition, sleep, and interdisciplinary planning among coaches, parents, and stakeholders should be emphasized to support young athletes' holistic development and well-being during the adolescent growth spurt.